2011
DOI: 10.3758/s13423-011-0109-6
|View full text |Cite
|
Sign up to set email alerts
|

Catching the mind in flight: Using behavioral indices to detect mindless reading in real time

Abstract: Although mind wandering during reading is extremely common, researchers have only recently begun to study how it relates to reading behavior. In the present study, we used a word-by-word reading paradigm to investigate whether it could be possible to predict in real time whether a participant would report mind wandering when probed. By taking advantage of the finding that reaction times to individual words vary based on reports of mind wandering (with participants being less affected by length, number of sylla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
125
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 21 publications
12
125
0
1
Order By: Relevance
“…We replicated the effects of a perseverative cognition induction (e.g., Ottaviani, Shapiro, & Fitzgerald, 2011; on target detection performance, showing decreased focus on the task and slower reaction times to target appearance indicative of difficulties in getting out of a state of heighted focus on ruminative and worrisome thoughts (Franklin, Smallwood, & Schooler, 2011;Ottaviani et al, 2013). Moreover, baseline HRV was associated with pre-to postinduction changes in perseverative cognition, confirming the previously reported association between cognitive inflexibility and autonomic rigidity (Ottaviani et al, 2013;2015a,b).…”
Section: Discussionsupporting
confidence: 74%
“…We replicated the effects of a perseverative cognition induction (e.g., Ottaviani, Shapiro, & Fitzgerald, 2011; on target detection performance, showing decreased focus on the task and slower reaction times to target appearance indicative of difficulties in getting out of a state of heighted focus on ruminative and worrisome thoughts (Franklin, Smallwood, & Schooler, 2011;Ottaviani et al, 2013). Moreover, baseline HRV was associated with pre-to postinduction changes in perseverative cognition, confirming the previously reported association between cognitive inflexibility and autonomic rigidity (Ottaviani et al, 2013;2015a,b).…”
Section: Discussionsupporting
confidence: 74%
“…Finally, the present results also add to a growing list of potential real-time markers of task-unrelated thought (Franklin, Broadway, Mrazek, Smallwood, & Schooler, 2013;Seli et al, 2012;Smallwood et al, 2012;Franklin, Smallwood, & Schooler, 2011;Smallwood, Brown, Tipper, et al, 2011;Reichle, Reineberg, & Schooler, 2010;Smallwood, McSpadden, Luus, & Schooler, 2008). Along with eye-tracking measures, our neural marker has the relative advantage that no overt behavioral response is required.…”
Section: Discussionmentioning
confidence: 57%
“…Neurocognitive studies have linked mind wandering with attenuated sensory (Braboszcz & Delorme, 2011;Kam et al, 2011;O'Connell et al, 2009), cognitive (Smallwood, Beach, Schooler, & Handy, 2008), and affective (Kam, Xu, & Handy, 2014) processing of stimuli. Moreover, previous research showed that people exhibit irregular eye movements and blink patterns during periods of mindless reading (Franklin, Smallwood, & Schooler, 2011;Reichle, Reineberg, & Schooler 2010;Smilek, Carriere, & Cheyne, 2010;Uzzaman & Joordens, 2011). The costs of mind wandering are widespread and extend beyond conventional experiments to important real-life activities such as learning.…”
mentioning
confidence: 99%
“…Mind wandering has been linked to impaired reading comprehension (Feng, D'Mello, & Graesser, 2013;Franklin et al, 2011;Reichle et al, 2010;Smallwood, 2011;Smallwood et al, 2004), worse knowledge retention (Farley, Risko, & Kingstone, 2013;Thomson, Smilek, & Besner, 2014), poorer memory for online lectures (Szpunar, Khan, & Schacter, 2013), lower exam and SAT scores (Lindquist & McLean, 2011;Unsworth, McMillan, Brewer, & Spillers, 2012), and diminished recall (Feng et al, 2013;Metcalfe & Xu, 2016;Smallwood, McSpadden, & Schooler, 2007). When we disengage from tasks requiring high levels of processing-for instance, reading or word encoding-our ability to process and perform the task worsens (Feng et al, 2013;Foulsham, Farley, & Kingstone, 2013;Smallwood et al, 2003).…”
mentioning
confidence: 99%